Screening Endophytes of Neem Leaf that Potential Anti-Anthrax through Tests of Anti Staphylococcus Aureus - Khuzyia Rizqi Triavi Ananda; Sunarno Sunarno; Muhamad Fikri Zulfikar; Hafsah Avisha; Muhamad Nastain; Ridwan Abdullah (Biosaintifika: Journal of Biology & Biology Education, 2018)
Anthrax is a deadly disease caused by Bacillus antracis that damages the lymphatic and vascular systems of animals and humans. Anthrax prevention in Indonesia has been done but has many shortcomings among them is a lot of dead animal raises after vaccination and relatively expensive. The azadirachtin bioactive compound produced by neem endophytic microbes is known to inhibit the growth of B. anthracis bacteria, thus potentially as an anti-anthrax agent. Other bacteria that have the same pathogens as B. antrachis are Methycillin Resistant Staphylococcus aureus (MRSA) so that it is used as a research object. The aim of this research is to obtain the active biomaterials from selected neem leaf endophytes to be tested in S. aureus MRSA as bacteria with Anthrax pathogens. The method used in this research is the isolation, selection, and extraction of NeemÂ  endophytes. The process of isolation is done by growing on the general media and the selection process on special media. The bioactive extraction process uses 1000 rpm centrifuge and screening on MRSA culture medium. Inhibitory zone tests were used to determine the effect of endophytic biopsy in inhibiting MRSA growth. The result of the research is that the bioactive endophytes of neem are able to inhibit MRSA growth which is characterized by the formation of drag zone around the endophytic bioactive. Thus it can be concluded that the use of neem endophytes can be a new solution to eradicate the presence of anthrax disease in the livestock and people in Indonesia with safe research methods, relatively inexpensive and ineffective vaccine replacements.